Dhamma Preaching and Political Transition in Burma/Myanmar (2011-2021). A Transient Popular Practice in a Time of Radical Buddhist Nationalism - Bénédicte Brac de la Perrière (Moussons)
This paper examines the passion for public Buddhist preaching that moved Yangon night’s scene during the transitional years (2011-2021) in light of the outburst of radical Buddhist nationalism that then prevailed, shaped by the emergence of a new monastic led organization for the “defense of national religion” (Mabatha). Built on observations dating back to the mid of the 2010s, the analysis deals with the impact of political regime change on religious life and with the instrumentalization of Buddhist preaching for nationalist mobilization.